Universally nondiverging Grüneisen parameter at critical points - Soares, Samuel M. [UNESP]; Squillante, Lucas [UNESP]; Lima, Henrique S.; Tsallis, Constantino; De Souza, Mariano [UNESP] (American Physical Society (APS), 2025)
According to Boltzmann-Gibbs (BG) statistical mechanics, the thermodynamic response, such as the isothermal susceptibility, at critical points (CPs) presents a divergent-like behavior. An appropriate parameter to probe both classical and quantum CPs is the so-called Grüneisen ratio Γ. Motivated by the results reported in [Phys. Rev. B 108, L140403 (2023)10.1103/PhysRevB.108.L140403], we extend the quantum version of Γ to the nonadditive q-entropy Sq. Our findings indicate that using Sq at the unique value of q restoring the extensivity of the entropy, Γ is universally nondiverging at CPs. We unprecedentedly introduce Γ in terms of Sq, being BG recovered for q→1. We thus solve a long-standing problem related to the illusory diverging susceptibilities at CPs.